THE PALEOCENE AND EOCENE IN THE RUSSIAN PART OF WEST EURASIA - Akhmets'ev M.A.; Beniamovski V.N. (My University, 2006)
Biostratigraphic charts of marine Paleocene and Eocene in the European and West Siberian parts of Russia include the unified zonations of nannoplankton, planktonic and benthic foraminifers, dinocysts, radiolarians, diatoms, and palynomorphs of higher plants. These regional zonations summarize comprehensive data on the Lower Paleogene, which have been obtained by paleontologists and biostratigraphers in the last century. In the content and resolution degree, they represent a solid basis for geological and paleogeographic consideration and characterize the time succession of diverse biotic and abiotic events. On the other hand, the depicted biotic events have been controlled by successive tectonic, paleogeographic, and paleoclimatic events, because organisms determining contents of biostratigraphic zones changed not only in the course of evolution, but also in response to transformation of surroundings. As elements of general communication systems, epicontinental seas of the Paleogene have been interconnected via straits and seaways, which promoted interchange of water masses and biotas belonging to the Tethys, Atlantic or Arctic oceans, and inner seas. Size and configuration of the seas and seaways changed under influence of tectonic processes and eustatic events of epeirogenic or regional origin. Widening, narrowing, and cessation of communication ways have been responsible for different-scale changes in sedimentation and biotic environments. New materials on the Paleogene in a vast territory of Russian sector of West Eurasia offer an opportunity to revise somewhat the dynamics of climatic changes in the Northern Hemisphere during the Early Cenozoic, which characterize the terminal phase of transition from the warm to cold biosphere of the Earth. © MAIK "Nauka/Interperiodica" 2006.
Keywords: PALEOCENE; PALEOCLIMATE; PALEOGEOGRAPHY; RUSSIAN SECTOR OF WEST EURASIA; SEDIMENTOLOGY; TECTONICS; ZONAL BIOSTRATIGRAPHY; Кайнозой::Палеоген::Эоцен; Cenozoic::Paleogene::Eocene